Sampling challenges in a study examining refugee resettlement - Sulaiman-Hill, C.; Thompson, Sandra (BioMed Central, 2011)
Background. As almost half of all refugees currently under United Nations protection are from Afghanistan or Iraq and significant numbers have already been resettled outside the region of origin, it is likely that future research will examine their resettlement needs. A number of methodological challenges confront researchers working with culturally and linguistically diverse groups; however, few detailed articles are available to inform other studies. The aim of this paper is to outline challenges with sampling and recruitment of socially invisible refugee groups, describing the method adopted for a mixed methods exploratory study assessing mental health, subjective wellbeing and resettlement perspectives of Afghan and Kurdish refugees living in New Zealand and Australia. Sampling strategies used in previous studies with similar refugee groups were considered before determining the approach to recruitment.Methods. A snowball approach was adopted for the study, with multiple entry points into the communities being used to choose as wide a range of people as possible to provide further contacts and reduce selection bias. Census data was used to assess the representativeness of the sample. Results. A sample of 193 former refugee participants was recruited in Christchurch (n = 98) and Perth (n = 95), 47% were of Afghan and 53% Kurdish ethnicity. A good gender balance (males 52%, females 48%) was achieved overall, mainly as a result of the sampling method used. Differences in the demographic composition of groups in each location were observed, especially in relation to the length of time spent in a refugee situation and time since arrival, reflecting variations in national humanitarian quota intakes. Although some measures were problematic, Census data comparison to assess reasonable representativeness of the study sample was generally reassuring.Conclusions. Snowball sampling, with multiple initiation points to reduce selection bias, was necessary to locate and identify participants, provide reassurance and break down barriers. Personal contact was critical for both recruitment and data quality, and highlighted the importance of interviewer cultural sensitivity. Cross-national comparative studies, particularly relating to refugee resettlement within different policy environments, also need to take into consideration the differing pre-migration experiences and time since arrival of refugee groups, as these can add additional layers of complexity to study design and interpretation.